Benzene Exposure in Workers From a Waste Oil Regeneration Plant During Ordinary Activities by Air and Biological Monitoring - Campo, Laura; Boniardi, Luca; Olgiati, Luca; Polledri, Elisa; Mercadante, Rosa; Fustinoni, Silvia (La Medicina del Lavoro, 2024)
Background: In the regeneration of waste oil, a strategical technological process for the European Union circular economy action plan, exhausted oils are regenerated to produce high performing oil bases. Aim of this work was to assess the exposure to benzene in plant workers during ordinary activities. Methods: 59 workers, potentially exposed to benzene, and 9 administrative workers from an Italian plant were monitored for the whole work shift with personal air samplers; urinary benzene (BEN-U) and S-phenyl mercapturic acid (SPMA) were measured by mass spectrometry methods in end-shift urine samples. Different job tasks were identified among workers. Results:Median (minimum-maximum) airborne exposures to benzene were